Social impacts of renewable energy in Germany: Size, history and alleviation - Jochen Diekmann; Barbara Breitschopf; Ulrike Lehr (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2016)
[Introduction] The support of renewable energy in electricity generation has been subject to much debate. Tariffs or premiums for renewable electricity generation have turned out as the instrument of choice in 23 EU member states and in more than 100 countries globally. But the financing of RE as well as the resulting burden sharing of additional costs from RE based surcharges differ tremendously by country. Germany has taken early action in the support of renewables. Additional costs from guaranteed prices meanwhile amount to 18.7 billion Euro (2014) and have nearly doubled since 2010 (see below). This amount is paid by end-consumers of electricity, by means of the so-called EEG (German abbreviation of the renewable-energy-law) surcharge. In 2015 this surcharge amounted to 6.170 ct/kWh and the surcharge for 2016 has been announced in October 2015 to be 6.354 ct/kWh (ÜNB 2015). The level of the surcharge is influenced by several factors. Final demand of energy intensive industry is exempt or on a lower surcharge, not to distort international competitiveness. This mechanism, however, increases the burden on those consumers, which are not exempt. Total additional costs are also determined by the difference between the fixed tariff for renewables and the prices they can fetch on the electricity market. Generally low prices at the electricity exchange, which are partly induced by the high share of renewable, lead to a large difference increasing the total surcharge. Like other electricity taxes or surcharges, the RE surcharge is regressive, too. For some household higher electricity prices are more than a mere nuisance; the increase in expenditures for electricity decreases the budget for other purposes by a noticeable amount. In addition, low income households often own less efficient appliances, and have fewer possibilities to react to rising electricity prices. These effects have been discussed in the literature for Germany (cf. Bardt, Niehues, Techert 2012a & b;. Neuhoff et al. 2012; Neuhoff et al. 2013a; Bardt, Niehues 2013; Grösche, Schröder 2013; Lehr, Drosdowski 2013; Frondel, Sommer 2014; Heindl et al. 2014; Heindl 2014; Lehr, Drosdowski 2015). International studies also confirm regressive effect of duties or levies on electricity prices (EEA 2012; Flues, Thomas 2015; Heindl, Löschel 2015). The regressive distribution effects of the EEG surcharge is generally considered relatively low (Grösche, Schröder 2013). Especially for households with very low income is the financial burden of the levy noticeable. With an annual electricity consumption of a household of 3,500 kWh the monthly impact of the EEG surcharge including VAT payable in 2015 amounts to 21 Euro. The paper brings together several strands of results based on research from the research project “ImpRES – Impact of Renewable Energy Sources in Germany”, supported by the Federal Ministry for Economic Affairs and Energy in Germany1. The paper explains the development of additional costs in RE electricity generation, which are part of the annual monitoring process and report Breitschopf et al. different years. It shows the distribution effects of the additional costs, with a particular focus on low income households and it reflects alternative financing mechanisms and their respective distribution effects.
Keywords: 330